LAPORAN KASUS : PYOMETRA PADA ANJING GOLDEN RETRIEVER - Yohanes T. R. M. R. Simarmata; Anita Kartini Lakapu; I Dewa Made Anom (JURNAL KAJIAN VETERINER, 2020)
Pyometra in dogs is a condition of the accumulation of purulent material in the uterus of female dogs caused by hormonal imbalances resulting in bacterial infections and excess fluid production in the uterus. A female Golden Retriever named Merry, age 4 years old, having her address at Jln. Raya Dharmasaba Denpasar with complaints of a limp dog, anorexia, issued a thick reddish-colored discharge from the genitals and smelly. Based on the results of systematic clinical examination and the results obtained that the temperature of the dog is 38.1 ℃ (normal), pulsus frequency 120x/minute and the frequency of breathing 40x/ minute. At the time of inspection and palpation of the large abdomen, the nipple comes out. In a complete blood test conducted at Anom Animal Clinic showing the results of Leucosytosis (an increase in white blood cells) which indicates the incidence of bacterial infection, the dog is diagnosed with pyometra after being supported also by X-ray examination results showing radiopaque on the abdomen and ultrasound results showing the uterus anechoic. Dogs treated by surgery to remove the ovary and uterus (ovaryohysterectomy) and continued administration of antibiotics and analgesics. On the 9thday after surgery the incision wound had dried, the skin fused well, and was no longer removing the discharge from the genitals.